MENINGKATKAN KEMAMPUAN MENULIS CERITA FANTASI DENGAN PENGGUNAAN VIDEO CERITA - Made Sri Indriani (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2019)
This Classroom Action Research (PTK) aims (1) to find out the steps to improve the ability to write fantasy stories by using video stories for Grade VII 3 students of Undiksha Middle School, (2) knowing the increase in students' ability to write fantasy stories through video stories for grade VII students 3 Undiksha Laboratory Middle School, and (3) know students' responses to the use of video stories in improving fantasy story writing skills in class VII 3 Undiksha Laboratory Middle School. The subjects in this study were students of class VII 3 Middle Undiksha Laboratory. The objects of this study are steps to improve the ability to write fantasy stories using story videos in Grade VII 3 students of Undiksha Laboratory Middle School, increase students 'ability to write fantasy stories through video stories in Grade VII 3 students of Undiksha Laboratory Middle School, and students' responses to the use of video stories in improving fantasy story writing skills in class VII 3 Undiksha Laboratory Middle School. Data collection methods used in this study were observation, tests, questionnaires and interviews. Data were analyzed with descriptive-qualitative and descriptive-quantitative techniques. The results of this study indicate that, (1) based on the results of observations made, it can be said that the steps of implementing learning by the teacher are already classified as good / good. This can be seen from the assessments given by researchers or observers when observing the teaching teacher. (2) the use of video stories can improve students' ability to write fantasy stories. This can be seen in the comparison of classical average scores, namely in the pre-action classical average score of 68.14 (sufficient), the first cycle obtained a classical average score of 76.66 (good), whereas in the second cycle the classical average value of students to 82.95 (good); (3) students give very positive and positive responses to the use of video stories in learning to write fantasy stories.Keywords : writing skills, fantasy stories, the use of story video mediaABSTRAKPenelitian Tindakan Kelas (PTK) ini bertujuan (1) mengetahui langkah-langkah meningkatkan kemampuan menulis cerita fantasi dengan menggunakan video cerita pada siswa kelas VII 3 SMP Laboratorium Undiksha, (2) mengetahui peningkatan kemampuan siswa menulis cerita fantasi melalui video cerita pada siswa kelas VII 3 SMP Laboratorium Undiksha, dan (3) mengetahui respons siswa terhadap penggunaan video cerita dalam meningkatkan keterampilan menulis cerita fantasi  di kelas VII 3 SMP Laboratorium Undiksha. Subjek dalam penelitian ini adalah siswa kelas VII 3 SMP Laboratorium Undiksha. Objek penelitian ini adalah langkah-langkah meningkatkan kemampuan menulis cerita fantasi dengan menggunakan video cerita pada siswa kelas VII 3 SMP Laboratorium Undiksha, peningkatan kemampuan siswa menulis cerita fantasi melalui video cerita pada siswa kelas VII 3 SMP Laboratorium Undiksha, dan respons siswa terhadap penggunaan video cerita dalam meningkatkan keterampilan menulis cerita fantasi  di kelas VII 3 SMP Laboratorium Undiksha. Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi, tes, kuesioner dan wawancara. Data dianalisis dengan teknik deskriptif-kualitatif dan deskriptif-kuantitatif. Hasil penelitian ini menunjukkan bahwa, (1) berdasarkan hasil observasi yang dilakukan, dapat dikatakan bahwa langkah-langkah pelaksanaan pembelajaran yang dilakukan guru sudah tergolong baik/bagus. Hal ini dapat dilihat dari penilaian yang diberikan peneliti atau observer saat mengamati guru mengajar. (2) penggunaan video cerita dapat meningkatkan kemampuan menulis cerita fantasi siswa. Hal ini dapat dilihat dalam perbandingan skor rata-rata klasikal, yakni pada pratindakan skor rata-rata klasikal 68.14 (cukup), siklus I memperoleh skor rata-rata klasikal 76,66 (baik), sedangkan pada siklus II nilai rata-rata klasikal siswa menjadi 82,95 (baik); (3) siswa memberikan respons sangat positif dan positif terhadap penggunaan video cerita dalam pembelajaran menulis cerita fantasi.Katakunci: kemampuan menulis, cerita fantasi, penggunaan media video cerita